2011
DOI: 10.1007/s12272-011-0403-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of megastigmane sesquiterpenes from the silkworm (Bombyx mori L.) droppings and their promotion activity on HO-1 and SIRT1

Abstract: The silkworm (Bombyx mori L.) droppings were extracted with 80% aqueous MeOH, and the concentrated extract was partitioned in succession with EtOAc, n-BuOH, and H(2)O. From the EtOAc fraction, five megastigmane sesquiterpenes were isolated through repeated silica gel and ODS column chromatography. According to the results of spectroscopic data, such as NMR, MS, and IR, the chemical structures of the isolated compounds were determined as (3S,5R,8R)-3,5-dihydroxymegastigma-6,7-dien-9-one (1), (S)-dehydrovomifoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…1) were identified by comparing their spectral data to those in the literature and were identified as clovane-2 β ,9 α -diol ( 3 ) (Collado et al 1998), alepterolic acid ( 4 ) (Braun and Breitenbach 1977), anticopalic acid ( 5 ) (Villegas Gómez et al 2009), (3 S ,5 R ,6 S )-trihydroxy-7 E -megastigmen-9-one ( 6 ) (Park et al 2011), β -amyrin ( 7 ) (Okoye et al 2014), Vitamin E ( 8 ) (Matsuo and Urano 1976), piliostigmin ( 9 ) (Ibewuike et al 1996), (+)-epicatechin ( 10 ) (Foo et al 1996), quercetin ( 11 ), quercitrin ( 12 ) (Aderogba et al 2013), Afzelin ( 13 ) (Aderogba et al 2013), 3-hexenyl-1-O- β -D-glucopyranoside ( 14 ) (Lee et al 2005), stigmasterol ( 15 ), and β -sitosterol glucoside ( 16 ) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…1) were identified by comparing their spectral data to those in the literature and were identified as clovane-2 β ,9 α -diol ( 3 ) (Collado et al 1998), alepterolic acid ( 4 ) (Braun and Breitenbach 1977), anticopalic acid ( 5 ) (Villegas Gómez et al 2009), (3 S ,5 R ,6 S )-trihydroxy-7 E -megastigmen-9-one ( 6 ) (Park et al 2011), β -amyrin ( 7 ) (Okoye et al 2014), Vitamin E ( 8 ) (Matsuo and Urano 1976), piliostigmin ( 9 ) (Ibewuike et al 1996), (+)-epicatechin ( 10 ) (Foo et al 1996), quercetin ( 11 ), quercitrin ( 12 ) (Aderogba et al 2013), Afzelin ( 13 ) (Aderogba et al 2013), 3-hexenyl-1-O- β -D-glucopyranoside ( 14 ) (Lee et al 2005), stigmasterol ( 15 ), and β -sitosterol glucoside ( 16 ) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The NMR spectra were measured on a Varian NMR System-500 or INOVA-500 spectrometer, at 500 MHz for 1 H NMR and 125 MHz for 13…”
Section: General Experimental Procedurementioning
confidence: 99%
“…The chemical investigation on the L. racemosa leaves collected at Kien Giang province, Viet Nam led to the isolation of ten compounds including the new one (1) by the use of efficient separation techniques ( Figure 1). The known compounds were identified as myricetin (2) [6] [10], gallic acid (8) [11], kaempferol (9) [12] and (3S,5R,6S,7E)-3,5,6trihydroxy-7-megastigmen-9-one (10) [13] via spectroscopic data analysis and comparison with those reported in the literature. In the 1 H NMR spectrum, the two anomeric proton signals at δ H 4.89 (a broad singlet, H-1) and 4.84 (a doublet, J = 1.0 Hz, H-1) showed that the two 1-OH and 1-OH groups were at the axial positions.…”
mentioning
confidence: 99%
“…[23][24][25] CONCLUSION High-speed counter-current chromatography (HSCCC) has successfully been applied for separation of (S)-dehydrovomifoliol using a two-phase solvent system of n-hexane-ethyl acetate-methanol-water (1:5:1:5, v=v) in 400 min single run where 23 mg of (S)-dehydrovomifoliol with 95% purity was obtained from 1 g crude sample of Nitraria sibirica Pall. The present study demonstrated that HSCCC is a powerful method in separation and isolation of bioactive compounds from natural products.…”
Section: Structural Identificationmentioning
confidence: 99%